La transferencia de construcciones reflexivas en situaciones de contacto en Pamplona - García Uriz , Eneko (Huarte de San Juan. Filología y Didáctica de la Lengua, 2018)
The following work has been carried out as a result of the question of whether due to the linguistic contact existing in the city of Pamplona (Navarra) between Spanish and Basque, there has been a transfer of this type of structures from Castilian to Basque or, on the contrary, they have been extended by means of another type of structure not usually considered as reflexive. For this we have analyzed the discourse of four young people of different linguistic profiles: a man and a woman euskaldunzahar and, on the other hand, a man and a woman euskaldunberri. Advancing the results obtained, we have observed that both in the speakers of L1 Basque and those of L1 Spanish, there has been some transfer of this type of constructions, possibly due to recent loans that have caused that besides a lexical loan, it is also syntactic.